Effect of guideline revisions by the Swiss Society of Hypertension on blood pressure control in hypertensive patients from primary care - Stéphanie Giezendanner; Peter Tschudi; Jörg Leuppi; Thomas Dieterle; Andreas Zeller (Swiss Medical Weekly, 2020)
BACKGROUND